Pembelajaran Kewirausahaan dan Komitmen Individu Pengaruhnya Terhadap Motivasi Berprestasi dan Minat Usaha Bagi Siswa SMK di Kota Makassar - Taslim Dangnga; Mustari Mustari; Romansyah Sahabuddin (Seminar Nasional LP2M UNM, 2019)
This study aims to analyze the influenceentrepreneurshiplearning and individual commitment to achievement motivation and business desire of thevocational high school students in Makassar city, South Sulawesi Province. The kind of research used is explanatory research. The total sample determined through purposive sampling method As many as 200 students.This study using the equipment analysis structural equation modeling. The research results explained that: 1) entrepreneurship Learning and individuals commitment have a direct influence which significant, in partial and simultaneously to achievement motivationof the vocational high school students, 2) entrepreneurship learning, individuals commitment and achievement motivation have a direct influence which significant,in partial and simultaneously tobusiness desireof the vocational high school students, 3) entrepreneurship learning and individuals commitment have a indirect influence to business desire through achievement motivation students, 4) achievement motivation have a influence which significant to business desire student.